Efficient finite element modelling of litz wires in toroidal inductors - Jay Panchal (Wiley, 2021)
Abstract Accurate understanding of losses and frequency‐dependent winding parameters have been an important aspect for selecting the right configuration of stranded conductors in power‐electronic inductors. An approach for modelling frequency‐dependent parameters of a winding with twisted wire bundles in toroidal inductors using a multi‐axial sliced finite element (FE) modelling approach is presented here. A 2D magnetodynamic FE problem is solved in several axial and radial slices of the inductor, accounting for the twisted conductor bundles by varying the conductor positions in the slices. Case studies are presented for different levels and pitch lengths of twisting. The approach is validated against 3D FE simulations in the case of 3–4 parallel strands and against measurements in the case of 75, 105 and 125 strands, which would be impossibly heavy for conventional 3D FE tools. The results provide insight into the effect of strand grouping, twisting levels and twisting pitch on the frequency‐dependent resistance of windings.